EFFECT OF DIFFERENT SOIL TYPES ON GROWTH AND PRODUCTIVITY OF EUPHORBIA LATHYRIS L. A HYDROCARBON YIELDING PLANT: Life Science-Botany - GARG, JOLLY; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2012)
Energy security is one of the most pressing challenges of the 21st century. A shift to next-generational fuels and increased use of renewable source of energy are increasingly being considered as viable options. Euphorbia lathyris is one of the most-suitable species that falls into the category of hydrocarbon yielding plants. This plant is suitable to grow in arid and semiarid climate. Addition of gravel to the sand considerably enhanced the plant height, fresh weight and dry weight. Maximum hexane, methanol and total extractables were also favoured by the addition of gravel.